Quantification of specific microbial functional guilds in Arctic permafrost soil - Walter, Deborah (Jihočeská univerzita, 2019)
The quantity of specific bacterial and archaeal groups were determined in permafrost soils. The selected groups were quantified by quantitative polymerase chain reaction (qPCR) of specific genes: total archaea (16SrRNA gene), methanogenic archaea (mcrA gene), nitrogen fixators (nifH gene) and denitrifiers (nosZ gene). The quantities of these groups were compared between different soil horizons and furthermore correlations between the quantity of gene copies and basic soil parameters were computed.
Quantification of specific microbial functional guilds in Arctic permafrost soil
Keywords: Arctic; permafrost; soil horizons; microbial guilds; qPCR; nifH; nosZ; mcrA; 16SrRNA; quantitative analysis; correlation computations; Arctic; permafrost; soil horizons; microbial guilds; qPCR; nifH; nosZ; mcrA; 16SrRNA; quantitative analysis; correlation computations